A class of iterated fast decodable space-time codes for 2n Tx antennas - Markin, Nadya (2012)
We present an iterative construction of algebraic space-time codes. Starting from a division algebra D, we show how to embed it into a larger ring A = A(D) and give conditions for A to be a new division algebra. Starting from a quaternion division algebra D1, we thus obtain a sequence D1 ⊂ D2 ⊂… of division algebras where Di = A(Di−1). Each of the Di can be used as an underlying structure to build a space-time Ci. Furthermore, the iteration step is done such that fast-decodability of the original code is preserved. We illustrate our technique by creating an iterative version of the Silver code.